Preparation method and application of chemically modified titanium-based sensor

By chemically modifying the titanium-based sensor, the existing titanium content detection methods are solved, and high sensitivity and wide range of titanium content detection are achieved, which is suitable for sample detection at different concentration levels.

CN119438343AActive Publication Date: 2025-02-14NAT JEWELRY TESTING CENT (GUANGDONG) CO LTD

Patent Information

Application Number
CN202411825336.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-14
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing titanium content detection methods have problems such as insufficient sensitivity, narrow detection range and high detection limit for low concentration titanium, which is difficult to meet the wide range detection requirements of titanium content in actual samples from low to high.

Method used

The chemically modified titanium-based sensor is used to enhance the selective adsorption ability of titanium ions by modifying nanomaterials and modifying functional molecules on the titanium electrode. Specific steps include pretreatment of the titanium electrode, nanographene modification and polypyrrole functional molecular modification.

Benefits of technology

The detection of titanium content with high sensitivity and wide concentration range is achieved, and the concentration of titanium ion can be accurately detected in the range of 10 pM to 100 mM, which significantly improves the detection sensitivity of titanium ions and the accuracy of analysis results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119438343A_ABST
    Figure CN119438343A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a chemically modified titanium-based sensor, which comprises the following steps: pretreatment of a titanium electrode: polishing the surface of the titanium electrode to be smooth and flat, and carrying out ultrasonic cleaning and drying; and chemical modification of the titanium electrode: firstly carrying out nano material modification on the pretreated titanium electrode, and then carrying out functional molecule modification. The invention further discloses a chemically modified titanium-based sensor, application of the chemically modified titanium-based sensor and a method for detecting the titanium content. According to the chemically modified titanium-based sensor provided by the method, the selective adsorption capacity to titanium ions is improved, the accuracy and the reliability of an analysis result are improved, high-sensitivity detection of the titanium content can be realized, and the concentration range is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal content detection, and specifically relates to a preparation method and application of a chemically modified titanium-based sensor. Background Art

[0002] With the growing demand for novel materials and innovative designs in the contemporary jewelry market, titanium jewelry has become an important material in the jewelry manufacturing industry due to its light weight, high strength and hypoallergenic properties. It is also increasingly favored by consumers and designers, driving a significant increase in demand for titanium jewelry. Therefore, the development of effective titanium content detection technology is crucial to ensuring the quality and performance of jewelry. It not only helps consumers identify genuine titanium jewelry, but also ensures that manufacturers comply with industry standards and regulatory requirements, and also has a positive impact on the optimal use of materials.

[0003] Traditional methods for detecting titanium content mainly include inductively coupled plasma mass spectrometry (ICP-MS), X-ray fluorescence spectrometry (XRF) and atomic absorption spectrometry (AAS). Although these technologies play an important role in the field of analysis, they usually require expensive equipment, complex sample pretreatment or are only applicable to detection under specific conditions. For example, although ICP-MS can provide highly sensitive and accurate analysis results, its high cost and complex operation process limit its application in routine detection. Atomic absorption spectrometry (AAS) has high sensitivity and selectivity for the determination of titanium content, but this method is not only expensive in terms of instruments, but also has strict requirements on sample preparation. The sample needs to be digested into a solution state, and the matrix interference in the solution has a great influence on the measurement results, requiring complex matrix correction. As a non-destructive analytical technique, XRF can quickly determine the element content in jewelry, but its detection sensitivity for light elements is limited, and the results are easily affected by the surface state of the sample.

[0004] Electrochemical sensors have been widely used in metal ion detection due to their high sensitivity, good selectivity, and simple operation. The performance of the sensor can be further improved by chemically modifying the electrode. For titanium content detection, there is great potential in developing a suitable chemically modified titanium-based sensor.

[0005] At present, there have been some research reports on the electrochemical determination of titanium content. For example, some studies have used polarography to determine the titanium content, using the current signal generated by the reduction reaction of titanium ions on the electrode surface in a specific electrolyte system to determine the titanium content. However, the existing electrochemical method still has some problems in determining the titanium content. For example, although some methods have high sensitivity, the detection concentration range is narrow and cannot meet the wide range detection requirements of titanium content from low to high in actual samples; although some methods can achieve wide concentration range detection to a certain extent, the sensitivity is not ideal, and the detection limit for low concentration titanium is high. Summary of the invention

[0006] An object of the present invention is to provide a method for preparing a titanium-based sensor capable of detecting titanium content with high sensitivity and a wide concentration range in view of the above technical problems to be solved.

[0007] Another object of the present invention is to provide a titanium-based sensor prepared by the above method.

[0008] Another object of the present invention is to provide application of the titanium-based sensor.

[0009] Another object of the present invention is to provide a method for detecting titanium content.

[0010] In order to achieve the above object of the invention, the present invention provides a method for preparing a chemically modified titanium-based sensor, the method comprising the following steps: (1) Pretreatment of titanium electrode: polish the surface of titanium electrode to make it smooth and flat, and then perform ultrasonic cleaning and drying; (2) Chemical modification of titanium electrode: First, the pretreated titanium electrode obtained in step (1) is modified with nanomaterials, and then modified with functional molecules.

[0011] Preferably, the nanomaterial modification comprises: dispersing 3 g of graphene oxide in 500 mL of deionized water to form a 6 mg / mL graphene oxide dispersion, adding 200 mL of a 40% hydroiodic acid aqueous solution for reduction, ultrasonically treating at 60° C. for 5 hours to promote the reaction, centrifuging to obtain a nanographene precipitate, washing with ethanol and deionized water, and drying; adding 600 mg of nanographene powder to 100 mL of ethanol for ultrasonic dispersion to form a nanographene dispersion with a concentration of 6 mg / mL; completely immersing the pretreated titanium electrode in the nanographene dispersion for 12-24 hours, then taking out the electrode, and drying it at 60-80° C. for 2-4 hours to firmly attach the nanographene to the electrode surface to obtain a titanium / graphene electrode.

[0012] Preferably, the functional molecule modification includes: mixing pyrrole monomer and ethanol in a mass ratio of 1:10 to form a sol, stirring at 60°C for 2 hours and standing for 48 hours to form a PPy gel, evenly dropping 500 μL of PPy gel on the clean titanium / graphene electrode surface, drying at room temperature, and finally heat treating at 80°C to solidify the film.

[0013] On the other hand, the present invention also provides a chemically modified titanium-based sensor, which is prepared by the method of the present invention.

[0014] On the other hand, the present invention also provides the use of the chemically modified titanium-based sensor in detecting titanium content.

[0015] On the other hand, the present invention also provides a method for detecting titanium content, which comprises the step of using the chemically modified titanium-based sensor for detection.

[0016] Preferably, the method for detecting titanium content of the present invention comprises the following steps: (1) Drawing a working curve: Place the three-electrode system in an electrolytic cell containing standard titanium solutions of different concentrations, add supporting electrolytes, buffer solutions, and organic complexing agent solutions, set potential parameters, start potential scanning, record current signals at different potentials, and draw a working curve based on the current signals and the corresponding titanium ion concentrations to ensure that the peak current shows a good linear relationship with the titanium ion concentration. (2) Sample detection: The actual sample is processed into a solution form suitable for detection to ensure that the titanium in the sample exists in the form of ions. The three-electrode system is placed in the sample solution, and potential scanning and current signal measurement are performed under the same experimental conditions as when drawing the working curve. According to the measured current signal, the corresponding titanium ion concentration is found from the working curve, thereby realizing the detection of the titanium content in the sample. The three-electrode system includes the chemically modified titanium-based sensor described in the present invention as a working electrode, an Ag / AgCl electrode as a reference electrode, and a platinum wire electrode as a counter electrode.

[0017] In this method, since the dissolution peak current and the titanium ion concentration show a good linear relationship within a certain range, the corresponding titanium ion concentration can be found through the working curve to accurately detect the titanium content in the sample.

[0018] Preferably, in step (1), the potential parameter is -0.2 V as the enrichment potential, the enrichment time is 2 minutes, the dissolution potential scanning range is set to -0.5 V to 0.5 V, and the scanning rate is set to 50 mV / s.

[0019] Preferably, in step (1), the supporting electrolyte is potassium chloride solution, preferably at a concentration of 1.0 mol / L. The buffer is HAc-NaAc, preferably at a pH of 4.0. The organic complexing agent solution is 5-Br-PADAP, preferably at a concentration of 4.0 mmol / L.

[0020] The titanium-based electrochemical electrode prepared by the present invention has enhanced selective adsorption capacity for titanium ions through chemical modification. This modified electrode can more effectively distinguish titanium ions from other interfering ions that may exist, thereby achieving more accurate titanium detection in a complex sample matrix. Combined with the use of an organic complexing agent, the method of the present invention can significantly improve the detection sensitivity of titanium ions. The complex formed by the organic complexing agent and the titanium ion produces an obvious current response during the electrochemical scanning process, making it possible to detect low-concentration titanium ions. In addition, the method of the present invention can accurately detect the concentration of titanium ions in a wide concentration range (from 10pM to 100mM), and can be applied to sample detection at different concentration levels. Through specific chemical modification and the selection of an organic complexing agent, the method of the present invention achieves highly selective detection of titanium ions, reduces the interference of other coexisting ions, and improves the accuracy and reliability of the analysis results. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Adsorption-stripping voltammograms of titanium electrodes chemically modified with nanographene or polypyrrole.

[0022] Figure 2 The adsorption-stripping voltammograms at different enrichment potentials.

[0023] Figure 3 The adsorption-stripping voltammograms at different enrichment times.

[0024] Figure 4 The adsorption-stripping voltammograms of different titanium solution concentrations.

[0025] Figure 5 The adsorption-stripping voltammograms at different pH values.

[0026] Figure 6 The adsorption-stripping voltammograms of different complexing agent concentrations.

[0027] Figure 7 The adsorption-stripping voltammogram shows whether it contains interfering ions. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific examples. It should be understood that the following examples are only used to illustrate the present invention, rather than to limit the scope of the present invention.

[0029] Example 1: Preparation method of chemically modified titanium-based sensor This embodiment describes in detail the preparation process of a titanium-based electrochemical sensor, which utilizes a chemically modified titanium-based electrode to improve the selective adsorption capacity of titanium ions.

[0030] 1. Pretreatment of titanium electrode (1) Material selection and cutting: Select high-purity titanium material (purity ≥ 99.95%) and cut it into titanium electrodes of the required size, with a size of 1 cm × 1 cm.

[0031] (2) Surface grinding: Use sandpaper from low mesh to high mesh (such as 200 mesh, 400 mesh, 600 mesh, 800 mesh and 1000 mesh) to grind the surface of the titanium electrode until the surface is smooth and flat.

[0032] (3) Ultrasonic cleaning: The polished titanium electrode is cleaned by ultrasonic cleaning (frequency 40KHz) in ethanol and ultrapure water for 15-30 minutes to remove impurities and oil stains on the surface, and then blown dry in a nitrogen atmosphere for use.

[0033] 2. Chemical modification of titanium electrode (1) Nanomaterial modification Graphene oxide (GO) was prepared by the Hummers method. 3g of GO was dispersed in 500mL of deionized water to form a 6mg / mL GO dispersion. 200mL of 40% (mass concentration) hydroiodic acid aqueous solution was added for reduction. Ultrasonic treatment (frequency 40KHz) was performed at 60℃ for 5 hours to promote the reaction. Nanographene precipitation was obtained by centrifugation at 9000rpm for 20 minutes, and washed twice with ethanol and deionized water. It was placed in a vacuum drying oven and taken out after drying at 60℃ for 4 hours. 600mg of nanographene powder was added to 100mL of ethanol and ultrasonically dispersed at 40KHz for 30 minutes to form a nanographene dispersion with a concentration of 6mg / mL. The pretreated titanium electrode was completely immersed in the nanographene dispersion for 12-24 hours. The electrode was then taken out and dried in an oven at 60-80℃ for 2-4 hours to make the nanographene firmly attached to the electrode surface.

[0034] (2) Functional molecule modification Polypyrrole (PPy) is a conductive polymer with good redox properties, which makes it easier for titanium ions to adsorb and complex on the electrode surface, thereby achieving selective adsorption of titanium ions. Polypyrrole film was prepared on the titanium electrode by the sol-gel method.

[0035] Pyrrole monomer and ethanol were mixed in a mass ratio of 1:10 to form a sol, stirred at 60 °C for 2 hours and allowed to stand for 48 hours to form a gel. Then, 500 μL of PPy gel was evenly drop-coated on the cleaned titanium / graphene electrode surface, dried at room temperature, and finally heat-treated at 80 °C to solidify the film.

[0036] Example 2: Method for detecting titanium content using a chemically modified titanium-based sensor 1. Preparation of instruments and reagents (1) Instruments An electrochemical workstation (Autolab, Metrohm, Switzerland) was set up to apply potential and measure current signals. A three-electrode system was prepared, including the chemically modified titanium-based sensor prepared in Example 1 as a working electrode, an Ag / AgCl electrode as a reference electrode, and a platinum wire electrode as a counter electrode.

[0037] (2) Reagents Supporting electrolyte solution: Potassium chloride solution is selected as the supporting electrolyte with a concentration of 0.1 - 1.0 mol / L.

[0038] Buffer solutions with pH values ​​ranging from 2.0 to 5.0: preparation of buffer solutions with different ratios of HAc-NaAc Organic complexing agent: heterocyclic azo reagents such as pyridine azo, thiazole azo, pyrazole azo (5-Br-PADAP) (TAR) Standard titanium solution: Prepare a series of standard titanium solutions with different concentrations ranging from 10pM to 100mM for drawing the working curve.

[0039] 2. Drawing of working curve (1) Preparation of electrolytic cell: The three-electrode system is placed in an electrolytic cell containing standard titanium solutions of different concentrations, and electrolyte and organic complexing agent solutions are added. A series of Ti(IV) complexes of different concentrations are enriched at constant potential under stirring conditions.

[0040] (2) Potential setting: Set the potential scanning range and scanning rate on the electrochemical workstation. The enrichment potential is preferably -0.2 V, the scanning rate is 20-100 mV / s (preferably 50 mV / s), and the enrichment time is 2 minutes.

[0041] (3) Potential scanning: Start the potential scanning, and the dissolution potential scanning range is -0.5V to 0.5V. Record the current signal at different potentials. When the potential at which the titanium ion undergoes redox reaction is reached, a corresponding current peak will be generated.

[0042] (4) Data recording and analysis: Based on the recorded current signal and the corresponding titanium ion concentration, a working curve is drawn. In a wide concentration range, the peak current and the titanium ion concentration show a good linear relationship.

[0043] 3. Sample testing (1) Sample preparation: Process the actual sample into a solution form suitable for detection to ensure that the titanium in the sample exists in ionic form.

[0044] (2) Potential scanning: Place the three-electrode system in the sample solution and perform potential scanning and current signal measurement under the same experimental conditions as when drawing the working curve.

[0045] (3) Concentration determination: Based on the measured current signal, the corresponding titanium ion concentration is found from the working curve to detect the titanium content in the sample.

[0046] Example 3: Effect of chemical modification of titanium electrode with nanographene or polypyrrole on dissolution peak signal The Ti / GNSs / PPy prepared in Example 1 and Ti (titanium electrode without any chemical modification), Ti / GNSs (titanium electrode modified with GNSs nanomaterials only (i.e., omitting the step of “functional molecule modification” in Example 1)), and Ti / PPy (titanium electrode modified with PPy only (i.e., omitting the step of “nanomaterial modification” in Example 1)) were exposed to 100 μM Ti 4+ Adsorption and stripping voltammetry curves in HAc-NaAc (pH 4.0) and 4mmol / L 5-Br-PADAP mixed electrolyte. Figure 1 As shown in Figure 2, the peak currents of bare Ti (curve a) and Ti / GNSs (curve b) do not change much. The peak current signal of Ti / PPy (curve c) is larger than that of curve a and curve b, which indicates that the polypyrrole film is beneficial to the 4+ The peak current of Ti / GNSs / PPy (curve d) increased significantly because the deposited polypyrrole film and GNSs had a synergistic effect, which effectively increased the electrode surface area, facilitated the adsorption and complexation of titanium ions on the electrode surface, and thus made Ti 4+ The dissolution signal on Ti / GNSs / PPy was significantly increased.

[0047] Example 4: Effect of different enrichment potentials on dissolution peak signals This example investigates the effect of different enrichment potentials on the peak signal of titanium ion dissolution. The supporting electrolyte used in the experiment is potassium chloride solution with a concentration range of 1.0 mol / L. 4mmol / L 5-Br-PADAP is selected as an organic complexing agent, and the HAc-NaAc buffer solution with a pH of 4.0 is used. In a solution containing 100μM titanium ions, the effect of different enrichment potentials between -0.5V and 0.5V on the peak current of titanium ion reduction is explored based on the above conditions.

[0048] Figure 2 As shown in the figure, as the enrichment potential increases from -0.5V to 0.5V, the reduction peak current gradually increases and reaches a maximum value at -0.2V. When the potential is further increased to -0.1V, the reduction peak current begins to decrease. This shows that the enrichment potential has a significant effect on the electrochemical response signal of titanium ions, so the enrichment potential is set to -0.2V to optimize the detection sensitivity of titanium ions. This finding is consistent with the basic principle of electrochemical enrichment, that is, the appropriate enrichment potential can effectively increase the concentration of the target substance on the electrode surface, thereby enhancing the current response.

[0049] Example 5: Effect of different enrichment times on dissolution peak signals This example investigates the effect of enrichment time on the reduction peak current of titanium ions. The results are shown in Figure 3 . The detection conditions of this embodiment are based on those of Example 4. The results show that within the enrichment time range of 0 to 5 minutes, as the cumulative time increases from 0 to 2 minutes, the reduction peak current of titanium ions increases significantly, indicating that the titanium ions enriched on the electrode surface gradually increase. As the enrichment time increases from 2 minutes to 5 minutes, the reduction peak current increases very slowly, which may indicate that the 2-minute enrichment time has reached the maximum detection amount that the effective detection area of ​​the electrode can load. Taking both sensitivity and analysis time into consideration, the enrichment time is set to 2 minutes.

[0050] Example 6: Effect of different titanium solution concentrations on dissolution peak signal This example investigates the ability of chemically modified titanium-based sensors to detect titanium ions at different concentrations. Figure 4 A is the titanium-based sensor prepared in Example 1 in a titanium ion solution with medium concentration (30μM, 50μM, 100μM, 120μM, 160μM, 220μM, 320μM), and the current signal increases with the increase of metal ion concentration, and Figure 4 Medium B at low concentrations (10pM, 20pM, 40pM, 80pM, 100pM, 120pM, 150pM) and Figure 4Medium C also has a good linear relationship at high concentrations (1mM, 2mM, 4mM, 8mM, 10mM, 12mM, and 16mM), which indicates that the titanium-based electrochemical sensor has a good one-step detection capability for titanium ions and performs well in both high and low concentration ranges.

[0051] Example 7: Effect of different buffer pH on dissolution peak signal This example investigates the effect of buffer pH on the reduction peak current of titanium ions. The results are shown in Figure 5 . Buffer solutions with pH values ​​of 2.0 to 5.0 were prepared from 200.0 mmol / L acetic acid and sodium acetate solutions (HAc-NaAc) in different proportions. In the pH range of 2.0 to 5.0, the reduction peak current at pH 4.0 was larger. As the pH further increased from 4.0 to 5.0, the reduction peak current gradually decreased. The pH of the buffer solution is a key influencing factor for titanium ion detection. The pH of 4.0 has a small measurement error and a large reduction peak current, so the pH of the HAc-NaAc buffer solution is preferably 4.0.

[0052] Example 8: Effect of complexing agent concentration on dissolution peak signal The reduction current of Ti(5-Br-PADAP)4 on the titanium electrode has a certain relationship with the concentration of 5-Br-PADAP in the sample. When the concentration is lower than 4 mmol / L, the reduction current increases with the increase of 5-Br-PADAP concentration. Figure 6 However, if the concentration of 5-Br-PADAP continues to increase, the reduction peak of 5-Br-PADAP will affect the reduction peak of Ti(5-Br-PADAP)4, resulting in an increase in the background current near the reduction peak of Ti(5-Br-PADAP)4, so 4mmol / L 5-Br-PADAP is taken as the optimal concentration.

[0053] Example 9: Effect of interfering ions on dissolution peak signals Figure 7 The titanium-based electrochemical sensor prepared in Example 1 contains interfering ions (Ni² + 、Co² + 、Fe³ + 、Cu² + 、Fe² + Mg² + 、Ca² + 、Mn² + or Cl - The adsorption and dissolution voltammetry curves of titanium complexes in electrolytes with ion concentrations of 100 μm are shown in Figure 2. Figure 7 As shown, Ti 4+The dissolution peak current deviation of the complex did not exceed 2.8%, the peak position did not change significantly, and no other dissolution peaks appeared, indicating that the electrochemical sensor has good selectivity.

[0054] Example 10: Precision of electrochemical determination of titanium ions at different concentrations This example evaluates the precision of the electrochemical method of the present invention in determining different concentrations of titanium ions. In the experiment, the titanium ion standard solution was directly added to the electrolyte solution to prepare low concentration (50pM), medium concentration (50μM) and high concentration (50mM) titanium ion solutions. In these solutions, intra-day repeated measurements, that is, the same sample was measured 5 times in a day, and inter-day measurements, that is, the same sample was measured for 5 consecutive days. By calculating the intra-day and inter-day coefficients of variation of different concentrations of titanium ions, the precision of the method was comprehensively investigated, and the results are shown in Table 1.

[0055] The experimental results show that the intra-day coefficient of variation of titanium ions is less than 5.5%, and the inter-day coefficient of variation is less than 6.3%, which indicates that the electrochemical detection method of the present invention has good precision in measuring titanium ions of different concentrations.

[0056] Table 1. Precision (n=5)

[0057] Example 11: Electrochemical method for determining the recovery rate of titanium ions at different concentrations This example investigates the use of the electrochemical method of the present invention for determining the recovery rate of titanium ions. After adding low concentration (50pM), medium concentration (50μM) and high concentration (50mM) titanium ion standard solutions to the electrolyte solution, a recovery experiment was performed by measuring the concentration of titanium ions in the solution before and after adding the titanium ion standard solution.

[0058] The calculation formula of relative recovery is: .

[0059] The results are shown in Table 2. The recovery rates of titanium ions at different concentrations ranged from 97.0% to 107.6%, and the maximum coefficient of variation was 5.0%, indicating that the electrochemical detection method of the present invention has good accuracy.

[0060] Table 2. Titanium ion recovery rate (n=5)

Claims

1. A method for preparing a chemically modified titanium-based sensor, characterized in that The method comprises the following steps: (1) Pretreatment of titanium electrode: polish the surface of titanium electrode to make it smooth and flat, and then perform ultrasonic cleaning and drying; (2) Chemical modification of titanium electrode: First, the pretreated titanium electrode obtained in step (1) is modified with nanomaterials, and then modified with functional molecules.

2. The method according to claim 1, characterized in that The nano material modification comprises: dispersing 3 g of graphene oxide in 500 mL of deionized water to prepare a 6 mg / mL graphene oxide dispersion, adding 200 mL of a 40% hydroiodic acid aqueous solution for reduction, ultrasonically treating at 60° C. for 5 hours to promote the reaction, centrifuging to obtain a nano graphene precipitate, washing with ethanol and deionized water, and drying; adding 600 mg of nano graphene powder to 100 mL of ethanol for ultrasonic dispersion to form a nano graphene dispersion with a concentration of 6 mg / mL; completely immersing the pretreated titanium electrode in the nano graphene dispersion for 12-24 hours, then taking out the electrode, and drying at 60-80° C. for 2-4 hours to firmly attach the nano graphene to the electrode surface to obtain a titanium / graphene electrode.

3. The method according to claim 2, characterized in that The functional molecule modification includes: mixing pyrrole monomer and ethanol in a mass ratio of 1:10 to form a sol, stirring at 60°C for 2 hours and standing for 48 hours to form a PPy gel, evenly dropping 500 μL of PPy gel on the clean titanium / graphene electrode surface, drying at room temperature, and finally heat treating at 80°C to solidify the film.

4. A chemically modified titanium-based sensor, prepared by the method according to any one of claims 1 to 3.

5. Use of the chemically modified titanium-based sensor according to claim 4 in detecting titanium content.

6. A method for detecting titanium content, comprising the step of using the chemically modified titanium-based sensor according to claim 4 for detection.

7. The method according to claim 6, characterized in that The method comprises the following steps: (1) Drawing a working curve: Place the three-electrode system in an electrolytic cell containing standard titanium solutions of different concentrations, add supporting electrolytes, buffer solutions, and organic complexing agent solutions, set potential parameters, start potential scanning, record current signals at different potentials, and draw a working curve based on the current signals and the corresponding titanium ion concentrations to ensure that the peak current shows a good linear relationship with the titanium ion concentration. (2) Sample detection: The actual sample is processed into a solution form suitable for detection to ensure that the titanium in the sample exists in the form of ions. The three-electrode system is placed in the sample solution, and potential scanning and current signal measurement are performed under the same experimental conditions as when drawing the working curve. According to the measured current signal, the corresponding titanium ion concentration is found from the working curve, thereby realizing the detection of the titanium content in the sample. The three-electrode system includes the chemically modified titanium-based sensor described in claim 4 as a working electrode, an Ag / AgCl electrode as a reference electrode, and a platinum wire electrode as a counter electrode.

8. The method according to claim 7, characterized in that In step (1), the potential parameter is -0.2 V as the enrichment potential, and the enrichment time is 2 minutes.

9. The method according to claim 7, characterized in that: In step (1), the dissolution potential scan range was set to -0.5 V to 0.5 V, and the scan rate was set to 50 mV / s.

10. The method according to claim 7, characterized in that In step (1), the supporting electrolyte is potassium chloride solution, the buffer solution is HAc-NaAc, and the organic complexing agent solution is 5-Br-PADAP.

Citation Information

Patent Citations

  • Preparation method and application of a TiO2 nanorod array thin-film electrode material

    CN103884756A

  • Nitrogen dioxide gas sensor and preparation method thereof

    CN104181209A

  • Nanostructured titanium multilayer electrode

    US20200340095A1

Cited By

  • Method for preparing TiO2 electrode through synergy of chemical etching and lysine modification

    CN121208093A